If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 2v = -4 Solving 2 + 2v = -4 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2v = -4 + -2 Combine like terms: 2 + -2 = 0 0 + 2v = -4 + -2 2v = -4 + -2 Combine like terms: -4 + -2 = -6 2v = -6 Divide each side by '2'. v = -3 Simplifying v = -3
| n-56=-22 | | 15+5x=16x-1-69 | | 13r+39= | | 2000*.75= | | 9x^2+18x+12=0 | | 5=4-3x | | 8c-15=49 | | 3(m+6)=2m | | 24/8= | | 3n^2-6n-1=0 | | -5(x-1)=20(x-10) | | 2000*0.75= | | -12.42=.03p | | 7-4x=3x+35 | | g-4=-13 | | 5(a+3b)=5a+15b | | x^2-16y=0 | | 5*16*15=b | | 5x-8=7x+12x | | y=4x-q | | -13+q=-40 | | 4(a+b)+6(b+2a)= | | 5.16.15=b | | 9.6m+6=300.5 | | h+2=13 | | -3x-71=103-9x | | 2(4v+9)=98 | | 4q+2q+3=6q-4 | | 6a+(-2c)+(-4a)+c= | | 2x^2-96=x | | 13x+15=13x-15 | | S-3=5s |